Occurrence of bilaterally impacted mandibular supernumerary teeth: A rare case report and review of literature - Pravesh Kumar Jhingta; Vinay Kumar Bhardwaj; Deepak Sharma; Nishant Negi; Sanjeev Vaid; Naresh Kumar (Wolters Kluwer Medknow Publications, 2016)
Supernumerary teeth are present in addition to the normal complement of teeth in permanent or deciduous dentitions. Incidence is high in a permanent dentition, affecting both the gender. They are more common in males, with the male to female ratio of 2:1. When the supernumerary teeth are causing problems such as, extensive resorption of adjacent teeth, hindering the eruption or malposition of permanent teeth, early surgical intervention is recommended. A case of bilaterally impacted supernumerary premolars was reported, when an orthopantomograph view was taken that revealed the presence of additional teeth impacted in relation to 35-36 and 45-46. Literature reports increased occurrence of the supernumeraries in the maxilla, but supernumerary premolars are more likely to develop in the mandible. Etiology of supernumerary teeth is ambiguous, and is due to the following conditions: Atavism or reversion, heredity, aberrations during embryologic formation, progress zone, and unified etiologic explanation.